Effect of lithium salts LiPF6 and LiBF4 on combustion properties of electrolyte with EC/PC/EMC under different pressures. (February 2022) - Qiao, Shibiao; Meng, Xiaokai; Cao, Weiguo; Yu, Shuo; Liu, Changcheng; Huang, Que
Abstract: In this paper, the combustion properties of ethylene carbonate/propylene carbonate/ethyl methyl carbonate (EC/PC/EMC) with LiPF6 or LiPF4 were studied by cone calorimeter under various environmental pressures in Hefei (100.09 kPa), Lijiang (76.11 kPa) and Lhasa (65.23 kPa), respectively. The impact of lithium salts and pressure on the significant fire parameters of electrolyte such as flame temperature, mass loss rate (MLR) and heat release rate (HRR) were analyzed to evaluate the degree of thermal hazard. The experimental results showed that with the decrease of ambient pressure, the peak HRR (pHRR) and total heat release (THR) declined, and the combustion duration increased significantly. In the steady combustion stage of electrolyte pool fire, the mean value of MLR had an exponential relationship with the external pressure. The error of HRR obtained by oxygen consumption (OC) calorimetry and stoichiometric thermochemistry (TC) theory was about 15%.